2013
DOI: 10.1038/nchembio.1356
|View full text |Cite
|
Sign up to set email alerts
|

Small molecules intercept Notch signaling and the early secretory pathway

Abstract: Notch signaling has a pivotal role in numerous cell-fate decisions, and its aberrant activity leads to developmental disorders and cancer. To identify molecules that influence Notch signaling, we screened nearly 17,000 compounds using automated microscopy to monitor the trafficking and processing of a ligand-independent Notch-enhanced GFP (eGFP) reporter. Characterization of hits in vitro by biochemical and cellular assays and in vivo using zebrafish led to five validated compounds, four of which induced accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 53 publications
5
59
0
Order By: Relevance
“…Based on these findings, H3K27me3 demethylation inhibitors might be an attractive therapy option in NOTCH1-induced T-ALL (or CLL). Finally, recent evidence suggests that it may be possible to inhibit Notch signaling by interfering with its trafficking in cancer cell secretory pathways (Ilagan and Kopan, 2013; Kramer et al, 2013). …”
Section: Therapeutic Targeting Of the Notch Pathway In Tumorsmentioning
confidence: 99%
“…Based on these findings, H3K27me3 demethylation inhibitors might be an attractive therapy option in NOTCH1-induced T-ALL (or CLL). Finally, recent evidence suggests that it may be possible to inhibit Notch signaling by interfering with its trafficking in cancer cell secretory pathways (Ilagan and Kopan, 2013; Kramer et al, 2013). …”
Section: Therapeutic Targeting Of the Notch Pathway In Tumorsmentioning
confidence: 99%
“…As distinct from BFA, which blocks protein transport from the ER to the Golgi and disrupts the trans-Golgi network (33), FLI-06 is a small molecule that blocks protein trafficking from the ER without disrupting the trans-Golgi network (32). As shown in Fig.…”
Section: Medium Than In Cells Precultured In 5 MM Kmentioning
confidence: 99%
“…To further determine the role of recycling in the recovery of hERG channels, we used the ER export inhibitor, FLI-06 (32). As distinct from BFA, which blocks protein transport from the ER to the Golgi and disrupts the trans-Golgi network (33), FLI-06 is a small molecule that blocks protein trafficking from the ER without disrupting the trans-Golgi network (32).…”
Section: Medium Than In Cells Precultured In 5 MM Kmentioning
confidence: 99%
“…Kramer and colleagues (43) developed a high-content screening assay to identify new regulatory proteins involved in Notch trafficking and processing in human cells. This assay relied on the generation of constitutively active, ligand-independent, NotchΔE-eGF stable cell lines in which nuclear eGFP staining was the surrogate measure of Notch activation.…”
Section: Notch Pathway Mutationsmentioning
confidence: 99%
“…The authors identified four γ-secretase modulators and the dihydropyridine FLI-06. They demonstrated that FLI-06 inhibits Notch trafficking early in the protein secretary pathway (43). Although the precise protein target of FLI-06 is yet to be determined, this finding is particularly important because new candidate targets/molecules regulating Notch trafficking are rapidly emerging in studies of Notch in other model organisms (44).…”
Section: Notch Pathway Mutationsmentioning
confidence: 99%